The Effect of Feeding with Different Percentages of Energy on the Growth Performance of Jowo Super Chicken - S. P. Lestari; O. Sjofjan; A. Furqon; Y. F. Nuningtyas; Muhammad Halim Natsir (Faculty of Animal Science, Universitas Brawijaya, 2022)
This study aims to determine the different levels both metabolic energy and protein treatments on growth performance of Jowo Super (JOPER) chickens. A total of 192 one-day-old chicks Jowo Super chickens (unsexed) were used in twelve-week trials. Prior to statistical analysis using analysis of variances (Anova) where least significance differences subjected using Duncan Multiple Test. The different levels of treatments on growth performance was not significance differ (p > 0.05). In summary, the metabolizable energy was recommended at 2880 kcal/kg (starter periods) and 2,950 kcal/kg (finisher). Feed intake, body weight gain, feed conversion ratio, and mortality was best in the 1707.17; 744.25; 2.53; 699.75, respectively.